Complete mitochondrial genome of Dong Tao chicken breed (Gallus gallus domesticus) of Vietnam - Nguyen, Dang Ton; Hai Ha, Nguyen; Phuong Nhung, Vu; Thanh Hoa, Nguyen Thi; Huyen Thuong, Ma Thi; Bich Ngoc, Tran Thi; Thuy Duong, Nguyen; Van Hai, Nong (Vietnam Journal of Biotechnology, 2020)
The complete mitochondrial genome of Dong Tao chicken breed (Gallus gallus domesticus, Dong Tao) was obtained by PCR and sequencing. The complete mitogenome was 16,783 bp in length, with the nucleotide composition for A, T, C, G was 30.29%, 23.75%, 32.48%, and 13.48%, respectively. The mitogenome of Dong Tao chicken contained a non-coding control region (D-loop), 2 rRNA genes, 13 protein-coding genes, and 22 tRNA genes. Phylogenetic analysis revealed that breed Dong Tao chicken breed was sister-close to G. gallus breed Guangxi, and paraphyletic to G. spadiceus, S. jabouillei, and a range of Chinese indigenous, ie. breeds Rugao and Taoyuan.